Tracking footprints of maize domestication and evidence for a massive selective sweep on chromosome 10 - Feng Tian; Natalie M. Stevens; Edward S. Buckler (2009)
Maize domestication is one of the greatest feats of artificial selection and evolution, wherein a weedy plant in Central Mexico was converted through human-mediated selection into the most productive crop in the world. In fact, the changes were so astounding that it took much of the last century to identify modern maize's true ancestor. Through modern genetic studies, the molecular basis of this evolution is being unraveled. Maize's new morphology and adaptation to diverse environments required selection at thousands of loci, and we are beginning to understand the magnitude and rates of these genetic changes. Most of the known major genes have experienced strong selection, but only small regions surrounding the selected genes exhibit substantially reduced genetic diversity. Here, we report the discovery of a large region on chromosome 10 involved in adaptation or domestication that has been the target of strong selection during maize domestication. Unlike previously described regions in the maize genome, 1.1 Mb and >15 genes lost genetic diversity during selection at this region. Finally, the prospects of a detailed understanding of maize evolution are discussed with consideration of both top-down and bottom-up approaches.